The Medaka Inbred Kiyosu-Karlsruhe (MIKK) panel - Fitzgerald, Tomas; Brettell, Ian; Leger, Adrien; Wolf, Nadeshda; Kusminski, Natalja; Monahan, Jack; Barton, Carl; Herder, Cathrin; Aadepu, Narendar; Gierten, Jakob; Becker, Clara; Hammouda, Omar; et al. (Genome biology, 2022)
Unraveling the relationship between genetic variation and phenotypic traits remains a fundamental challenge in biology. Mapping variants underlying complex traits while controlling for confounding environmental factors is often problematic. To address this, we establish a vertebrate genetic resource specifically to allow for robust genotype-to-phenotype investigations. The teleost medaka (Oryzias latipes) is an established genetic model system with a long history of genetic research and a high tolerance to inbreeding from the wild.
Gesehen am 12.04.2022